Understanding how long-term organic amendments increase soil phosphatase activities: Insight into phoD- and phoC-harboring functional microbial populations. (December 2019) - Luo, Gongwen; Sun, Bo; Li, Ling; Li, Minghui; Liu, Manqiang; Zhu, Yiyong; Guo, Shiwei; Ling, Ning; Shen, Qirong
Abstract: In context of the use of organic materials as alternatives for mineral fertilizer, it is important to understand how organic amendments influence soil extracellular phosphatase activities which accelerate the mineralization of organic phosphorus (P). To address this, the current study investigates the influence of organic amendments on acid (ACP) and alkaline (ALP) phosphatase activities in soils and how organic amendments influence these activities from the perspective of microbially-mediated pathways. Herein, a comprehensive meta-analysis of 599 measurements from 106 published studies around the world was performed as well as a field component sourced from a 30-year-old field experiment on fertilization. Based on meta-analysis, organic amendments increased average extracellular ACP and ALP activities by 22% and 53%, respectively, in comparison to the mineral-only fertilization. Observed increases in activities were consistent with significant increases in soil organic carbon (C), total nitrogen (N) and available P contents, and microbial biomass C and N pools. According to the data from the long-term field experiment, we found phoD -harboring species encoding ALP were more closely correlated with phoC -harboring species encoding ACP in organically amended soils, and more network hubs were also observed by organic amendment. Soil C:P and N:P ratios, and microbial biomass C were the main predictors of the abundance, diversity, and composition of the phoC - and phoD -harboring populations. Further analysis revealed that the soil C:P ratio was identified as the dominant predictor of potential ACP and ALP activities. Our work highlights the importance in understanding how soil C:N:P stoichiometry mediates phosphatase-harboring populations in order to determine the downstream consequences of using organic amendments for increasing phosphatase activities. Highlights: We performed a meta-analysis of 599 measurements from 106 published studies with organic amendment. Organic amendment increased soil phosphatase activity by 22%–53% than mineral-only fertilization. Phosphatase-harboring microbial populations were tested using phoD and phoC genes. Stronger co-occurrence pattern existed in the communities of organically amended soils. Soil C:P ratio and microbial biomass C were the crucial indicator of phosphatase activity.